A Longitudinal and Spatial Analysis Assessing Green Gentrification in Historically Disenfranchised Neighborhoods of Barcelona: Implications for Health Equity. (June 2017) - Cole, Helen; Triguero, Margarita; Connolly, James; Anguelovski, Isabelle
Abstract : Background: Municipal green space is generally regarded as beneficial for the health and well-being of urban residents due to reductions in pollution, increased social interaction, and encouragement of healthful behaviors. However, greening may also lead to "green gentrification", causing economic stressors and displacement among vulnerable populations. Little is known about how green gentrification processes may modify the relationship between green spaces and health outcomes. We evaluate the effects of new green spaces in socially vulnerable neighborhoods of Barcelona between 1990 and the early 2000s on the socioeconomic composition of areas surrounding these spaces and apply our findings to the development of a testable conceptual model for understanding the implications of our results for health equity. Methods: We consulted employees in appropriate city offices to understand the trajectory of greening in 5 contiguous districts in Barcelona. Combining OLS and GWR analysis together with a spatial descriptive analysis, we examined the evolution over time of six socio-demographic gentrification indicators in the areas in proximity to 18 green spaces constructed during our study period in comparison with the entire district. We related our findings to past models documenting the pathways by which access to green space is related to mental and physical health outcomes through a health equity frame. Results: Our results indicate distinct patterns by neighborhood, including that parks built in parts of the old town and in formerly industrialized neighborhoods of Barcelona seem to have experienced green gentrification. In contrast, most economically depressed areas and working class neighborhoods with less desirable housing stock that are more isolated from the city center gained vulnerable residents as they became greener, indicating a possible redistribution and higher concentration of vulnerable residents as neighborhoods undergo processes of urban (re)development. Our results indicate a potential for gentrification to moderate the relationship between green spaces and health. Conclusions: Although green spaces are thought to have a positive impact on health according to current models in the environmental justice and public health literature, the redistribution of vulnerable populations in the city due to the effects of green gentrification appear to have modified who may benefit from new green spaces. In addition, we hypothesize that stress associated with the gentrification process may lead to poorer mental and physical health among vulnerable residents, thereby having the potential to increase, rather than decrease, health inequity. We incorporate these findings into a modified, testable conceptual model, the Green Gentrification Health (In) Equity Model.